Length measures: proposal to understand the use of the standard ruler (Edma 0-6: Educación Matemática en la Infancia, 2021)
Children are usually familiar with the attribute of length. However, its measure with standard devices like rulers is not intuitive for them. The main obstacles are the lack of identification of the unit, as distance interval, as well as the role of the numbers contained in the ruler, with are not interpreted for the children as indicators of accumulation of the unit. Considering these difficulties, we propose that the use of the ruler need previous instruction, so it is designed a didactic sequence in which the standard ruler is being built from four others focused on these two elements: unit and numbers. We intend to achieve a better conceptualization of length measurements with ruler.
Keywords: Measurement; Metrology; Metric system; Geometry; Early Childhood Education; Primary education; Teaching methods